Dampak Alih Fungsi Lahan Pertanian Padi Menjadi Perkebunan Kelapa Sawit Terhadap Lingkungan, Ekonomi dan Sosial Budaya di Desa Jatibaru Kecamatan Bunga Raya Kabupaten Siak - Emilia Dharmayanthi; Zulkarnaini Zulkarnaini; Sujianto Sujianto (Universitas Riau, 2018)
Land conversion at Desa Jatibaru had widely impact on the rice planting area, it decrease rice productivity. A research conducted to determine the impact of land conversion from paddy fields to palm oil plantation at Desa Jatibaru, it affects not only to decreased of rice productivity but also to environment, economic, social and cultural impact .The objective of the research was to analyse the impact of land conversion from paddy fields to palm oil plantation. The research use Case study approach by using observation and in-depth interview methods. The result show that the number of animals and plants in paddy fields is higher than oil palm plantations. The conversion of paddy to oil palm plantations will have an impact on the sustainability of ecosystem diversity. The impact of land conversion on the economy is the larger financial income on oil palm farmers compared to wetland paddy farmers. The impact of land conversion to social and cultural is to give an increase on the social status of oil palm farmers and the diminishing of mutual cooperation and harvest activities in Jatibaru.